Transitional institutions, institutional complementarities and economic performance in China: A 'Varieties of Capitalism' approach - Joachim Ahrens; Patrick Jünemann (OrdnungsPolitisches Portal (OPO), 2010)
The paper focuses on institutional change and institution building as integral parts of economic transition in China. China's success, particularly compared with other advanced transition economies, implies a puzzling observation: China did not apply theoretically-derived policy recommendations. Instead, authorities followed a gradual, pragmatic approach to reform, decentralize, and transform the economy. Notable examples of non-orthodox policy measures, which worked effectively in China, include so-called transitional institutions such as the dual-track approach to industrial restructuring, anonymous banking, the establishment of special economic zones or the priority given to create competitive structures while postponing large-scale privatization of state-owned enterprises. Hence, it is not evident what kind of market economy will emerge in China in the long run. The paper aims at (i) applying the Varieties-of-Capitalism (VoC) framework to China and assessing its suitability in a transition context; (ii) addressing the question of what kind of market economy is emerging in China; (iii) analyzing the impact which the emerging type of capitalism will have on the economy's allocative and dynamic efficiency; and (iv) elaborating policy implications which may help generate or strengthen potential institutional complementarities in the long run.
Keywords: H0; O53; P2; P3; 330; institute; China; capitalism; Varieties of Capitalism; Systemtransformation; Institutioneller Wandel; Kapitalismus; Staatliche Einflussnahme; China